Performance Evaluation and Optimization of a Canvas Belt Cowpea Thresher for Small-Scale Farming Applications - Adanu, E. O.; Iya, S. A.; Yakubu, I. T.; Kabri, H. U. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
This study evaluates the performance of a canvas belt thresher designed specifically for cowpea, addressing post-harvest challenges in threshing efficiency, seed damage, and grain loss. Traditional threshers often lack precision for cowpea, leading to reduced yield and high labour demands. The constructed canvas belt thresher was tested at various drum speeds (200–1200 rpm) and moisture contents (10–14%) to determine its impact on threshing recovery, efficiency, cleaning ability, and seed integrity. Comparative performance was also assessed against a spike-tooth thresher, revealing the canvas belt thresher’s enhanced threshing efficiency (93.98%) and lower unthreshed grain percentage (6.02%) at optimal conditions. While the canvas belt thresher showed reduced throughput (91.33 kg/h) compared to the spike-tooth (181.89 kg/h), it minimized grain damage (3.83% vs. 11.54%) and achieved a higher threshing recovery rate (89.62%). Overall, the canvas belt thresher demonstrated effective threshing and cleaning for cowpea, although certain design refinements, such as covering the belt edges to reduce seed loss, could further enhance its efficiency and yield. This study highlights the potential of a canvas belt thresher for cowpea to support post-harvest processing, reduce losses, and improve yield quality in regions reliant on cowpea as a staple crop. Future research could investigate adjustments in belt configuration and speed control for further optimization.